Effects of Different Cell-Detaching Methods on the Viability and Cell Surface Antigen Expression of Synovial Mesenchymal Stem Cells - Kunikazu Tsuji Ph.D. (Cell Transplantation, 2017)
Flow cytometric analysis of cell surface antigens is a powerful tool for the isolation and characterization of stem cells residing in adult tissues. In contrast to the collection of hematopoietic stem cells, the process of enzymatic digestion is usually necessary to prepare mesenchymal stem cells (MSCs) suspensions, which can influence the expression of cell surface markers. In this study, we examined the effects of various cell-detaching reagents and digestion times on the expression of stem cell-related surface antigens and MSC functions. Human MSCs were detached from dishes using four different reagents: trypsin, TrypLE, collagenase, and a non enzymatic cell dissociation reagent (C5789; Sigma-Aldrich). Following dissociation reagent incubations ranging from 5 to 120 min, cell surface markers were analyzed by flow cytometry. Trypsin and TrypLE quickly dissociated the cells within 5 min, while collagenase and C5789 required 60 min to obtain maximum cell yields. C5789 significantly decreased cell viability at 120 min. Trypsin treatment significantly reduced CD44 + , CD55 + , CD73 + , CD105 + , CD140a + , CD140b + , and CD201 + cell numbers within 30 min. Collagenase treatment reduced CD140a expression by 30 min. In contrast, TrypLE treatment did not affect the expression of any cell surface antigens tested by 30 min. Despite the significant loss of surface antigen expression after 60 min of treatment with trypsin, adverse effects of enzymatic digestion on multipotency of MSCs were limited. Overall, our data indicated that TrypLE is advantageous over other cell dissociation reagents tested for the rapid preparation of viable MSC suspensions.